“O Almanach tudo desvenda... tudo ensina”: sociabilidades, mediação cultural e elementos cívico-educacionais nos impressos Brasil-Portugal (1899-1903) - Marques , Ana Luiza de Vasconcelos (2019)
ABSTRACT Based on three volumes of the Almanach Illustrado do Brasil-Portugal, which totals 610 pages permeated by illustrations, chronicles and a variety of texts destined to the PortugueseBrazilian intellectuals who had the intention to educate and civilize the readers, above all, observing the civic-educational elements present in the almanacs. Produced and edited in Lisbon, these almanacs circulated throughout Brazil, and although a considerable part of the collaborators were Portuguese descent, there was a marked presence of Brazilians in the main sections, as well as correspondents and collaborators spread throughout certain regions of the country. Under the bias of the interdisciplinary approach between cultural history and the history of education, through a qualitative research with a temporal cut from 1899 to 1903, it was emphasized the importance of understanding the civilizing element that substantiated the Portuguese-Brazilian historical relations in relation to sociability networks formation (SIRINELLI, 1996; GOMES, 1993) and the actuation of these intellectuals as cultural mediators (GOMES; HANSEN, 2006), learning with the knowledge of great researchers such as Justino Magalhães (2003, 2010), André Botelho (2002) and Norbert Elias (1993). Among the resources which were used, in addition to the consultation of periodicals published between the end of the nineteenth century and the beginning of the twentieth, BrazilPortugal: revista quinzennal illustrada is also analyzed, highlighting the numbers published in the year 1900, on commemorative matters produced to the IV Centenary of Discovery of Brazil. About the collective profile of Almanach's collaborators, the data point to a group mostly composed of male writers born in the 1850s, concentrating on the age group between 41 and 60 years old, of Portuguese nationality, in which all collaborated in at least one yournal beyond the almanacs and 94% had published books.As a criterion for selecting and analyzing the sources, the trajectory of the Portuguese and Brazilian intellectuals who linked themselves to the magisterium related to their professional activities, as a guideline for the materiality of the almanacs, regarding the categories of education, civilization and produced in the three annuals. It was considered that these categories are intertwined in a PortugueseBrazilian culture with an elitist and Eurocentric veneer, marked by the defense of national education, which had as its background the civilizing discourse, oriented towards progress and modernization. Education assumes the central place as an adequate instrument to attend to the moral and civic values of the society, along with the liberal, conservative and positivist criteria that cultivated and disseminated normative rules for the society in question. Thus, it is concluded that the Portuguese and Brazilian intellectuals in the figure of cultural mediators integrated in networks of sociability – constructed in multiple spatial-temporal dimensions – were involved in the pedagogical and civilizing mission to instruct the public to which they were destined, besides the limits of almanacs. These almanacs bring to light civic-educational elements that, through the propagation of a liberal culture, make possible the multiplication of political and cultural exchanges between Portugal and Brazil, having the language and the common language as an important element of connection and approximation between the two nations.